On the Importance of the World: Phenomenology in Maimonides's Guide of the Perplexed - Shuster, Martin (The journal of religion, 2019)
The article presents an essay regarding a phenomenology in the works of philosopher Maimonides and the importance of his text of the ontological category of world. Topics discussed include the certainty in the Quran and in the work of philosopher al-Ghazālī, the Greeks and philosopher Aristotle as the source of phenomenology, and the significance of worldhood to Maimonides.